The potentials of digestive caecum in mudflat snail Telescopium telescopium as a possible cadmium source for industrial application - Yap, Chee Kong; Ariffin, Noorhaidah; Nulit, Rosimah; Ibrahim, Mohd Hafiz; Peng, Shih Hao Tony; Yap, Chee Wah; Ng, Wai Kong (Ecronicon, 2019)
This paper cited the cadmium (Cd) data in the seven different soft tissues (foot, cephalic tentacles, mantle, muscle, gill, digestive caecum (DC) and remaining soft tissues) of mudflat snail Telescopium telescopium that were previously published by Yap and Noor-haidah [1]. These Cd data were re-evaluated from the point of the industrial use. The data were re-analyzed by using probability analysis and were calculated for bioaccumulation factor (BAF). In general, it was found that Cd levels were the highest in DC when compared to other different organs/soft tissues. Also, the Cd levels in the DC are comparable to habitat surface sediment based on BAF. This strongly indicated that DC is the main target organ for Cd storage and accumulation based on the accumulation pattern of Cd in the seven soft tissues. Therefore, it is suggested that DC of the mudflat snails is a possible Cd source for industrial application.